2018
DOI: 10.3390/su10114181
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ghana’s Comparative Advantage in Maize Production and the Role of Fertilizers

Abstract: Maize is one of the most important cereal crops produced and consumed in West Africa, but yields are far under their potential and the production gap leads to growing import bills. After the structural adjustment program, fertilizer subsidies again became a popular intervention to increase yields in most African countries. Ghana introduced fertilizer subsidies in 2008, with high government expenses. This study assesses the competitiveness of Ghanaian maize production and the significance of socio-economic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Farmers con rmed that such lower yield could be associated with the low rate of fertilizer application coupled with climate effects in Ghana in which this is consistent with the report described by previous papers (e. g., Ragasa et al 2013;Tanko et al 2016;Scheiterle and Birner 2018;Scheiterle et al 2019). A lower grain yield could be associated with poor soil and crop management practices in Ethiopia (Tesfahunegn et al, 2016).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Farmers con rmed that such lower yield could be associated with the low rate of fertilizer application coupled with climate effects in Ghana in which this is consistent with the report described by previous papers (e. g., Ragasa et al 2013;Tanko et al 2016;Scheiterle and Birner 2018;Scheiterle et al 2019). A lower grain yield could be associated with poor soil and crop management practices in Ethiopia (Tesfahunegn et al, 2016).…”
Section: Resultssupporting
confidence: 85%
“…A lower grain yield could be associated with poor soil and crop management practices in Ethiopia (Tesfahunegn et al, 2016). Existing literature also showed that the inorganic fertilizers are applied to nearly one half of the area planted with maize in Ghana (Ragasa et al 2013;Scheiterle and Birner 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the Eastern Region, the farmers reported that maize yield varied significantly between 0.25 and 5 tons ha -1 , with a mean value of 1.5 tons ha -1 . The mean and maximum maize yields in the study village of this region are lower than the estimated achievable yield potential of 6.0 tons ha -1 which is reported in the conditions of Ghana [ 6 , 60 ]. According to the respondents of this study, a higher maize yield was reported in the Eastern Region than in the Northern Region of Ghana (Tables 4 and 5 ), which could be associated with the severity of soil degradation and effects of climate variability.…”
Section: Resultsmentioning
confidence: 65%
“…Juxtaposing this with the average farm size, it can be concluded that the average farmer had obtained 4.79 bags (479 kg) of maize from an acre farm. Scheiterle and Birner (2018) estimated that high experience in farming and use of herbicides increases the probability of a farmer having yield above average (1.5 MT/ha). Table 2 shows the level of FAW infestation among the sampled farmers.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Although there has been a general increase in maize productivity in recent years primarily due to increase in area of land put under cultivation, increase access to improved seeds, fertilizers and improved technology through enhanced extension service, the increase in production are still below potential yield (MoFA, 2017). This shortfall can be attributed to a number of factors and require the efforts of all stakeholders in order to significantly reduce the gap (MoFA, 2017) and address food security challenges in West Africa (Scheiterle & Birner, 2018). Amidst the production shortfalls, Ghana has over the years introduced a number of policies in the agricultural sector towards improvement in the sector.…”
Section: Introductionmentioning
confidence: 99%